The prevalence of sexually transmitted infections in Papua New Guinea: a systematic review and meta-analysis. - Andrew Vallely; Andrew Page; Shannon Dias; Peter Siba; Tony Lupiwa; Greg Law; John Millan; David P Wilson; John M Murray; Michael Toole; John M Kaldor (PLoS ONE)
Background The potential for an expanded HIV epidemic in Papua New Guinea (PNG) demands an effective, evidence-based and locally-appropriate national response. As sexually transmitted infections (STIs) may be important co-factors in HIV transmission nationally, it is timely to conduct a systematic review of STI prevalences to inform national policy on sexual health and HIV/STI prevention. Methodology/principal findings We undertook a systematic review and meta-analysis of HIV and STI prevalences in PNG, reported in peer-reviewed and non-peer-reviewed publications for the period 1950-2010. Prevalence estimates were stratified by study site (community or clinic-based), geographic area and socio-demographic characteristics. The search strategy identified 105 reports, of which 25 studies (10 community-based; 10 clinic-based; and 5 among self-identified female sex workers) reported STI prevalences and were included in the systematic review. High prevalences of chlamydia, gonorrhoea, syphilis and trichomonas were reported in all settings, particularly among female sex workers, where pooled estimates of 26.1%, 33.6%, 33.1% and 39.3% respectively were observed. Pooled HIV prevalence in community-based studies was 1.8% (95% CI:1.2-2.4) in men; 2.6% (95% CI:1.7-3.5) in women; and 11.8% (95% CI:5.8-17.7) among female sex workers. Conclusions/significance The epidemiology of STIs and HIV in PNG shows considerable heterogeneity by geographical setting and sexual risk group. Prevalences from community-based studies in PNG were higher than in many other countries in the Asia-Pacific. A renewed focus on national STI/HIV surveillance priorities and systems for routine and periodic data collection will be essential to building effective culturally-relevant behavioural and biomedical STI/HIV prevention programs in PNG.